Common Environment Policies in Different Sustainability Paradigms: Evidence From the Baltic, Adriatic, and Black Seas - Zagonari, Fabio; Tsani, Stella; Mavrikis, Sotiris; Koundouri, Phoebe (Frontiers in Marine Science, 2018)
We develop a model for four sustainability paradigms (weak sustainability, a-growth, de-growth, strong sustainability) within a single framework that accounts for responsibility for nature and future generations and for intra- and inter-generational equality. The model is applied in three case studies: the Baltic, the Adriatic and the Black Sea with the aim to identify feasible sustainability solutions for shared seas under alternative sources of environmental pressure and cooperation strategies. The Baltic Sea is analysed as an example of pollution from agriculture, the Adriatic Sea as an example of over-exploitation of fish in fishery, and the Black Sea as an example of pollution from industry. Empirical results show that different cooperation strategies are feasible in each case and that they yield different results in different context. Also welfare implications vary between different cooperation strategies. The main policy implication of the analysis is twofold. Environmental conservation must be preferred to environmental innovation, where both intra- and inter-generational equity concerns are unessential. The choice of a different sustainability approaches must be combined with the feasibility of the differently required management institutions, while considerations of the sectoral sources of environmental pressure are essential.